2021
DOI: 10.12998/wjcc.v9.i17.4310
|View full text |Cite
|
Sign up to set email alerts
|

Acute liver failure with thrombotic microangiopathy due to sodium valproate toxicity: A case report

Abstract: BACKGROUND Sodium valproate is widely used in the treatment of epilepsy in clinical practice. Most adverse reactions to sodium valproate are mild and reversible, while serious idiosyncratic side effects are becoming apparent, particularly hepatotoxicity. Herein, we report a case of fatal acute liver failure (ALF) with thrombotic microangiopathy (TMA) caused by treatment with sodium valproate in a patient following surgery for meningioma. CASE SUMMARY A 42-year-old man w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Sodium valproate (2‐propylpentanoic acid; SV) is commonly used to control epilepsy, bipolar disorders, and migraines 6 . SV causes acute liver injury resulting in acute liver failure with thrombotic microangiopathy, hepatic encephalopathy in clinical subjects 7–9 . In experimental studies, SV has been reported to elevate liver marker enzymes in serum and induce oxidative stress mediated liver injury in rats 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…Sodium valproate (2‐propylpentanoic acid; SV) is commonly used to control epilepsy, bipolar disorders, and migraines 6 . SV causes acute liver injury resulting in acute liver failure with thrombotic microangiopathy, hepatic encephalopathy in clinical subjects 7–9 . In experimental studies, SV has been reported to elevate liver marker enzymes in serum and induce oxidative stress mediated liver injury in rats 10,11 .…”
Section: Introductionmentioning
confidence: 99%
“…VPA toxicity can occur with dose adjustments to reach therapeutic levels in patients with metabolic disorders, drug-drug interactions, or self-harm attempts [6]. Its toxic effects are seen in multiple organ systems such as the hematological, nervous, and digestive systems [7]. Long-term use of VPA may cause nausea, vomiting, anorexia, sedation, weight gain, hair loss, hepatotoxicity, encephalopathy, and myopathy [8].…”
Section: Introductionmentioning
confidence: 99%